"But He Could Not Warm Himself": Sexual Innuendo and the Place of 1 Kgs 1, 1-4. Issue 1 (2nd January 2018) - Schreiner, David B.
ABSTRACT: Springing off recent articles by Richard Hess and Russell Meek, this essay argues for the collaboration of vv. 1b and 4 to suggest that 1 Kgs 1, 1-4 is concerned with discussing David's impotency. In light of this physiological development, David's attendants embarked on a search for a virgin. The Sumerian folktale "The Old Man and the Young Girl" may provide illumination for such an endeavor as it testifies to a perception that young women could rejuvenate impotent men. As for Adonijah's pursuit of the throne, one can interpret a causative, albeit it implicit, relationship between 1, 1-4 and vv. 5ff. David's impotence rendered him unable to fulfill certain diplomatic duties, which had been a hallmark of his reign and rise to power. Such a development cast a shadow over the future of the administration, and ultimately, these four verses establish a sense of irony that will be revisited periodically throughout the history.